Protein metabolism and physical fitness are physiological determinants of body condition in Southern European carnivores - Santos, Nuno (2020)
The physiological significance of biometric body condition indices (bBCI) is poorly understood. We hypothesized that bBCI are composite metrics of nutritional physiology, physical fitness and health. To test this hypothesis, we first compared the performance of eight bBCI, using 434 Southern European carnivores from six species as a model system; and then identified, by non-destructive methods, the hematology and serum biochemistry correlates of three selected bBCI. Fulton’s K Index, Major Axis Regression Residuals and Scaled Mass Index were the only bBCI insensitive to the effect of sex and age. The most informative physiological parameters in explaining the variation of these bBCI were the albumin (Effect Size (ES) = − 1.66 to − 1.76), urea (ES = 1.61 to 1.85) and total bilirubin (ES = − 1.62 to − 1.79). Hemoglobin and globulins (positive) and cholesterol (negative) were moderately informative (0.9 <|ES|< 1.5). This study shows that most bBCI do not control for the effect of age and sex in Southern European carnivores. Our results support that bBCI are composite measures of physiologic processes, reflecting a positive gradient from protein-poor to protein-rich diets, accompanied by increased physical fitness. Biometric body condition indices allow the integration of ecologically relevant physiological aspects in an easily obtained metric.